Feasibility Analysis of Rubber and Oil Palm Farming in Sekernan District, Muaro Jambi Regency - Nurlina, Nurlina; Wahyuni, Ira; Damayanti, Yusma (JALOW | Journal of Agribusiness and Local Wisdom, 2025)
This research aims to (1) Describe the general condition of rubber and oil palm farming in Sekernan District, (2) Analyze the income generated from these farming activities, and (3) Evaluate the feasibility of rubber and oil palm farming in Sekernan District, Muaro Jambi Regency. The research location was chosen purposively in Bukit Baling and Suak Putat villages. A total of 68 farmers were selected using simple random sampling. The data collected include primary and secondary data, analyzed using descriptive analysis, farm income analysis, Revenue-Cost Ratio (R/C Ratio), and Capital Productivity (π/C Ratio). The results showed that: (1) Oil palm farming had higher land area, input use, and production compared to rubber farming. (2) Farmers’ income from oil palm was higher than from rubber farming, although both types of farming were still profitable. (3) Both rubber and oil palm farming were feasible based on R/C Ratio > 1 and π/C values above the current bank interest rate. Thus, farming activities are more profitable than saving in the bank. Keywords: Farm Feasibility, Farming Income, Rubber, Oil Palm